Importance of nonverbal communication tools in English professional language - Nosirova, Shoiraxon (The Lingua Spectrum, 2025)
This article explores the scientific study of the importance of nonverbal tools (facial expressions, gestures, body movements, distance, etc.) in the process of communication. On the example of professions such as doctors, teachers, military personnel, journalists and lawyers, the aim is to analyze the role of nonverbal signals in establishing relationships, improving efficiency and identifying emotions. Based on literature analysis and existing research, it can be said that since eye contact and open position reveal hidden concerns, nonverbal actions in doctors strengthen the relationship with patients and increase their level of satisfaction. In teachers, however, nonverbal tools improve student motivation and academic performance, such as by animating the lesson through gestures and facial expressions, which can increase students’ academic success by 30-65%. In military personnel, nonverbal signals are important in co-ordinating secret communication and collective action, as they provide quick and clear communication in the event of stress, for example, through hand gestures, commands that are not perceived by the enemy are issued. In journalists, nonverbal tools help to maintain neutrality in interviews and detect falsehood, since mimics and gestures increase informativeness and determine the effectiveness of communication by up to 90%. In lawyers, however, open position and eye contact increase credibility during the trial and affect the outcome of the case by 65-93%. The results show that nonverbal elements significantly affect professional success, accounting for 55-93% of communication. In conclusion, the study of reading and appropriate application of nonverbal means is recommended to professional people with the aim of preventing further cultural misunderstandings and achieving communication efficiency.